(untitled) (Molecular Medicine Communications, 2022)
Degenerative disc disease (DDD) is characterised by progressive intervertebral disc (IVD) inflammation that ultimately causes lower back pain. The available therapeutic approach for DDD is the management of pain and spinal infusion. In the present investigation, the rat needle punctured disc degeneration model was established under a fluoroscopically guided system, followed by human umbilical cord mesenchymal stem cells (hUC-MSCs) transplantation. The IVD degeneration was examined and confirmed by radiography, histology, and pain and inflammatory marker evaluation. A rat tail disc degeneration model was developed with three successive coccyx IVDs. The needle was inserted into the IVD under fluoroscopic guidance, and its tip was inserted through the lateral annulus fibrosus into the nucleus pulposus (NP) region, twisted 360o twice, and held for 30 seconds. To assess the IVD height from radiography images 2 weeks after disc puncture and MSC transplantation to evaluate the degree of IVD degeneration and regeneration, The pain and inflammatory molecular markers were quantified using qPCR. To assess the severity of IVD degeneration and regeneration, histology was performed using haematoxylin and eosin (H & E) and alcian blue staining. MSCs were successfully isolated from human umbilical cord tissue and exhibited fibroblast-like morphology. Radiographic imaging and histological analyses showed significant IVD degeneration after 2 weeks of injury, and the hUC-MSC group exhibited the restored NP region and significant presence of proteoglycans in contrast to the degenerated group. When compared to healthy IVDs, the molecular expression of pain and inflammatory genes was significantly increased on days 2 and 5, resulting in an immunomodulatory response and a marked IVD degeneration. Conversely, the hUC-MSC group at 2 and 5 days showed significantly downregulated expression of C-JUN, C-FOS, AKT, OPG, RANK, TLR4, and IL-1β compared to the degenerated IVDD group. Moreover, the hUC-MSCs-treated group indicated significant NP hydration. The preclinical transplantation of hUC-MSCs can potentially reduce the pain and inflammation caused by disc degeneration. Therefore, the therapy can ideally deal with all the manifestations that occur due to such debilitating DDD.